STRATEGI BADAN USAHA MILIK DESA (BUMDes) DALAM PENGEMBANGAN DESA WISATA DI DESA SEMPU KECAMATAN NGANCAR KABUPATEN KEDIRI - Angelina Alda Reza; Isnaini Rodiyah (Halu Oleo University, 2025)
This research aims to examine the strategies implemented by the Village-Owned Enterprise (BUMDes) in developing a tourism village in Sempu Village, Ngancar District, Kediri Regency. The research was conducted at BUMDes Sempu Mandiri, located in Sempu Village. This study employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The informants consisted of the Head of Sempu Village, the Director of BUMDes Sempu Mandiri, and village officials. The findings indicate that: a) the organizational strategy and objectives of BUMDes Sempu Mandiri are generally aimed at improving the village economy by optimizing local potential and encouraging community entrepreneurship; b) the program strategy involves the development of a tourism unit managed through village funds and digital promotion, although implementation has been less effective due to the IT team's lack of focus on a single tourism unit; c) the resource support strategy is carried out through collaboration with the government, private sector, academia, and media to enhance the management and development capacity of business units; and d) the institutional strategy shows that the organizational structure of BUMDes Sempu Mandiri is functioning properly, although coordination among business actors still needs improvement.